1996
DOI: 10.1093/clinids/22.1.14
|View full text |Cite
|
Sign up to set email alerts
|

The Positive Predictive Value of Isolating Coagulase-Negative Staphylococci from Blood Cultures

Abstract: We used four criteria to define true bloodstream infections after isolation of coagulase-negative staphylococci (CNS) from Isolator (Wampole Laboratories, Cranbury, NJ) blood cultures: (1) the patient's temperature was > or = 38 degrees C, (2) appropriate treatment was administered, (3) the physician diagnosed bloodstream infection or criteria for nosocomial bloodstream infection were met, and (4) at least one clinical sign or laboratory value was consistent with infection. Sixty (26.4%) of 227 episodes met th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
84
3
5

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(101 citation statements)
references
References 34 publications
8
84
3
5
Order By: Relevance
“…Some studies have suggested an association between S. epidermidis and nosocomial infections (Vuong & Otto 2002) with this species being identified in 74 to 92% of patients with bacteremias caused by CNS (Martin et al 1989). However, other studies have reported a series of infections caused by other CNS species (Herwaldt et al 1996), mainly S. haemolyticus which Simple scheme for the identification of human Staphylococcus species; +: positive; -: negative; +, -: positive or negative; ±: weak is the second most frequently detected species (Bannerman 2003). Since CNS are the etiological agents of a series of infectious processes, identification of these microorganisms is important for the determination of their physiopathological characteristics and clinical importance and for epidemiological studies, and has led to the publication of various studies analyzing identification methods for these bacteria (Knapp & Washington 1989, Bannerman et al 1993, Piccolomini et al 1994, Renneberg et al 1995, Ieven 1995, De Paulis et al 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested an association between S. epidermidis and nosocomial infections (Vuong & Otto 2002) with this species being identified in 74 to 92% of patients with bacteremias caused by CNS (Martin et al 1989). However, other studies have reported a series of infections caused by other CNS species (Herwaldt et al 1996), mainly S. haemolyticus which Simple scheme for the identification of human Staphylococcus species; +: positive; -: negative; +, -: positive or negative; ±: weak is the second most frequently detected species (Bannerman 2003). Since CNS are the etiological agents of a series of infectious processes, identification of these microorganisms is important for the determination of their physiopathological characteristics and clinical importance and for epidemiological studies, and has led to the publication of various studies analyzing identification methods for these bacteria (Knapp & Washington 1989, Bannerman et al 1993, Piccolomini et al 1994, Renneberg et al 1995, Ieven 1995, De Paulis et al 2003.…”
Section: Discussionmentioning
confidence: 99%
“…An urgent need also is the implementation of central- and clinically defined sepsis was present, and the other reason being that the prevalence of bloodstream infection due to CNS, i.e. Staphylococcus epidermidis, has been increasingly associated with clinically relevant episodes of bloodstream infections (19,(22)(23)(24). Pittet et al (22) and others have reported that candidal fungemia and polymicrobial infection are microbiological predictors of mortality in patients with hospital-acquired bloodstream infection (2,19,25).…”
Section: Discussionmentioning
confidence: 99%
“…A bloodstream infection was defined using previous guidelines from the Centers of Disease Control and Prevention (CDC) modified for the occurrence of coagulase-negative Staphylococci. 30 …”
Section: Study Design and Definitionsmentioning
confidence: 99%